Terapi Neuro Linguistic Programming (NLP) untuk meningkatkan resiliensi pada remaja dengan Non-Suicidal Self Injury (NSSI) - Azalia, Sabella Sacharissa; Pratitis, Niken Titi (Persona:Jurnal Psikologi Indonesia, 2020)
Abstract Adolescents with non-suicidal self-injury (NSSI) are vulnerable to resilience or resilience to their problems. Resilience is an important part for adolescents to have in order to overcome their problems. One of the psychological interventions that can be done is to increase resilience by using the Neuro-Linguistic Therapy Program (NLP), in which this therapy focuses on thinking patterns and information processing so that adolescents can practice independently when the desire to hurt themselves arises. This study aims to determine the effectiveness of NLP therapy to increase the resilience of adolescents with NSSI. This research is a quantitative study using a pre-experimental design approach with one group pretest-posttest design. The data collection method used was the Self-Harm Behavior Questionnaire (SHBQ) scale to determine the NSSI behavior in adolescents, and to use a resilience scale before and after therapy to measure the results of NLP therapy treatment. Participants in this study were students with NSSI behavior consisting of three female students and two male students. The results showed that NLP therapy was effective in increasing the resilience of students with NSSI. The implications and limitations of the study are discussed.Keywords: Adolescent Resilience; Neuro Linguistic Programming Therapy; Non-Suicidal Self Injury. AbstrakRemaja dengan non-suicidal self-injury (NSSI) rentan dengan ketahanan atau resilien dalam menghadapi permasalahannya. Resilien menjadi bagian penting untuk dimiliki remaja agar dapat mengatasi permasalahannya. Salah satu Intervensi psikologi yang bisa dilakukan adalah meningkatkan resiliensi dengan menggunakan terapi Neuro Linguistic Program (NLP), yang mana terapi ini berfokus pada pola pikir dan pengolahan informasi sehingga remaja dapat mempraktikkan secara mandiri di saat keinginan untuk menyakiti diri sendiri muncul. Penelitian ini bertujuan untuk mengetahui efektivitas terapi NLP untuk meningkatkan resiliensi remaja dengan NSSI. Penelitian ini berupa penelitian kuantitatif menggunakan pendekatan pre-experimental design dengan one group pretest posttest design. Metode pengumpulan data yang digunakan adalah skala Self Harm Behaviour Questionnare (SHBQ) untuk mengetahui perilaku NSSI pada remaja, serta menggunakan skala resiliensi sebelum terapi dan sesudah terapi untuk mengukur hasil dari perlakuan terapi NLP. Partisipan dalam penelitian ini adalah siswa yang memiliki perilaku NSSI yang terdiri dari tiga siswi perempuan dan dua siswa laki-laki. Hasil penelitian menunjukkan bahwa Terapi NLP efektif meningkatkan resiliensi siswa dengan NSSI. Implikasi dan keterbatasan penelitian dibahas.Kata Kunci: Non-Suicidal Self Injury; Resiliensi Remaja; Terapi Neuro Linguistic Programming